As práticas restaurativas na EPT à luz da perspectiva decolonial: um novo paradigma de formação docente - Amoretti, Magali Elis Pesamosca (2023)
This study seeks to analyze themes that permeate teacher training, as a praxis. To do so, it starts from the idea that one of humanity's greatest challenges may be to live harmoniously and that educational institutions are intense, plural communities, with diverse dynamics and with different relationships. In this bias, it seeks to understand Restorative Practices in the light of decolonial thinking in the continuing education processes of teachers at the Instituto Federal Farroupilha – IFFar. Specifically, the objective is to present considerations about restorative practices and their interlocution with decolonial thinking; to ponder on issues intertwined in the notion of care linked to restorative practices; to analyze the use of Restorative Practices in everyday educational life from the perspective of teachers who took the Basic Initiation Course in Restorative Practices offered by IFFar. In order to fulfill these objectives, a qualitative approach was used through a bibliographical review, in addition to documentary research and the application of an online questionnaire for teachers who took the Basic Course of Initiation in Restorative Practices, at IFFar. Data analysis will be performed using the Content Analysis method. Also proposed in this study is an analysis through the perspective of postcolonial and decolonial studies, for the recognition and appreciation of differences and diversities, since the restorative perspective tends to be a possible alternative to decolonize teaching and teaching.